Analisis Laju Dosis Radiasi Neutron Pada Pekerja Radiasi Menggunakan Surveymeter di Instalasi Radioterapi - Ida Bagus Putu Priastana Bawa; Ni Nyoman Ratini; Wayan Balik Sudarsana; Gusti Ngurah Sutapa; I Made Satriya Wibawa; I Gde Antha Kasmawan; Rozi Irhas (Kappa Journal, 2024)
The research was carried out at the Radiotherapy Installation at Hospital Prof. Dr. I.G.N.G. Work with the aim of knowing the value of the neutron radiation dose rate at the maximum point after the irradiation is carried out and knowing the value of the neutron radiation dose rate to radiation workers based on the Dose Limit Value permitted by BAPETEN. The research was carried out by measuring the neutron radiation dose rate using a neutron surveymeter at 7 different points with a photon beam of 10 MV energy. At point A, the average value of the neutron radiation dose rate at the maximum point was 6618.87 ± 959.50 µSv/h, at point B it was 1586.99 ± 113.95 µSv/h, at point C it was 1599.90 ± 210.98 µSv/h, at point D it is 1236.83±113.94 µSv/h, at point E it is 297.48±41.79 µSv/h, at point F it is 23.69±3.14 µSv/h h and at point G of 0.54 ± 0.44 µSv/h. Then the value of the equivalent dose rate of neutron radiation at each point is obtained, namely, at point A it is 1.8 µSv/h, at point B 3.2 µSv/h, at point C 3.5 µSv/h, at point D 2 .3 µSv/h, at point E 2.3 µSv/h, at point F 2 µSv/h and at point G 1.9 µSv/h, then the equivalent dose rate value is compared with 1/2 NBD of radiation workers of 5 µSv /h, then the equivalent dose rate value is still below 1/2 of the NBD of radiation workers and the SPO that applies at the Radiotherapy Installation at Hospital Prof. Dr. I.G.N.G. Ngoerah is indeed safe for radiation workers.